2016
DOI: 10.3389/fnins.2016.00321
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Type 2 (CB2) Receptors Activation Protects against Oxidative Stress and Neuroinflammation Associated Dopaminergic Neurodegeneration in Rotenone Model of Parkinson's Disease

Abstract: The cannabinoid type two receptors (CB2), an important component of the endocannabinoid system, have recently emerged as neuromodulators and therapeutic targets for neurodegenerative diseases including Parkinson's disease (PD). The downregulation of CB2 receptors has been reported in the brains of PD patients. Therefore, both the activation and the upregulation of the CB2 receptors are believed to protect against the neurodegenerative changes in PD. In the present study, we investigated the CB2 receptor-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 62 publications
(77 reference statements)
5
108
0
1
Order By: Relevance
“…Upon ROT administration, microglia-derived ROS such as superoxide, hydroxyl, and peroxynitrite has been shown to cause selective degeneration of SNc, owing to low levels of antioxidant defense and accompanying high levels of DA metabolism (Javed et al, 2016). More specifically, microglia derived ROS was found to be indispensable for ROT-induced DA degeneration (Gao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Upon ROT administration, microglia-derived ROS such as superoxide, hydroxyl, and peroxynitrite has been shown to cause selective degeneration of SNc, owing to low levels of antioxidant defense and accompanying high levels of DA metabolism (Javed et al, 2016). More specifically, microglia derived ROS was found to be indispensable for ROT-induced DA degeneration (Gao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the CB2R agonist β‐caryophyllene demonstrated neuroprotection by virtue of its anti‐inflammatory and antioxidant properties (Javed et al . ). Studies using leucine‐rich repeat kinase 2 (LRRK2)‐transgenic mice also demonstrated CB2 receptor as a potential pharmacological target to treat PD (Palomo‐Garo et al .…”
Section: Changes In the Endocannabinoid System In Neurodegenerative Dmentioning
confidence: 97%
“…Administration of CB2 agonist can reduce the infract size of the brain and motor functional deficits and restrain the production of adhesion factor and matrix metalloproteinases, inhibit the inflammatory response, and improve the microcirculation after cerebral ischemia (Fernández-Ruiz et al, 2007; Benito et al, 2008; Pini et al, 2012). The CB2 can be upregulated in multiple central nervous system diseases, such as Alzheimer's disease, Parkinson's disease, Huntington's disease, and stroke (Capettini et al, 2012; Javed et al, 2016). The CB2 signaling mechanism is associated with the activation of the phosphatidylinositol 3-kinase (PI3K–Akt) pathway (Molina-Holgado et al, 2002; Palazuelos et al, 2006; Fernández-Ruiz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%